2022
DOI: 10.3390/foods11213526
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Containing Tamarind Isolate Protein Potentiate the Satiety without Promoting the Anti-Inflammatory Effect in a Preclinical Model of Diet-Induced Obesity

Abstract: The study aimed to evaluate the nanoparticles (ECW) containing tamarind trypsin inhibitor (TTI) concerning the storage effect under different conditions on antitrypsin activity and the bioactive potential in a preclinical model. ECW was exposed to different pH and temperatures to evaluate the interaction between TTI and its encapsulating agents, monitored by antitrypsin activity. Wistar rats (n = 25) with obesity induced by diet were divided into groups: untreated; treatment with nutritionally adequate diet; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Among the studies, two were performed with peptides encapsulated in liposomes, with an in vivo study using mice with obesity induced by a high-fat diet [ 29 , 30 ]. For studies with proteins, two studies were found, in which the researchers used liposomes and polymeric nanoparticles, with an in vivo study in mice with obesity induced by a high-fat diet and a high-glycemic-index, high-load diet [ 31 , 32 ]. From these studies, it is possible to identify the limitations of using these molecules as candidates for their use in humans [ 18 , 19 , 26 ].…”
Section: Encapsulation Methods and Techniques Used To Enhance The Eff...mentioning
confidence: 99%
See 4 more Smart Citations
“…Among the studies, two were performed with peptides encapsulated in liposomes, with an in vivo study using mice with obesity induced by a high-fat diet [ 29 , 30 ]. For studies with proteins, two studies were found, in which the researchers used liposomes and polymeric nanoparticles, with an in vivo study in mice with obesity induced by a high-fat diet and a high-glycemic-index, high-load diet [ 31 , 32 ]. From these studies, it is possible to identify the limitations of using these molecules as candidates for their use in humans [ 18 , 19 , 26 ].…”
Section: Encapsulation Methods and Techniques Used To Enhance The Eff...mentioning
confidence: 99%
“…Costa et al [ 32 ] investigated the encapsulation of TTI through nanoprecipitation in an organic solvent to obtain efficient polymeric particles. It was observed that the interaction of the active with the encapsulating agents increased the stability of the inhibitor at a neutral pH and potentiated the activity of the protein concerning the effect on weight reduction in Wistar rats with obesity.…”
Section: Encapsulation Methods and Techniques Used To Enhance The Eff...mentioning
confidence: 99%
See 3 more Smart Citations